Exploring the intersection of EFL learning motivation and filial piety : a literature review - Wenxin, Lu; Joseph, Ramanair (Frontier Scientific Research Publishing Inc, 2025)
The global demand for English-proficient workers has increased EFL learning, but motivation issues have emerged, particularly in Eastern cultures where values differ from Western ideals. This study explores how filial piety, a core Eastern value, influences the motivation of Chinese EFL learners. By reviewing six studies from 2015 to 2024 through an integrative literature review, the paper finds that filial piety motivates learners to achieve social recognition and success in language learning. The findings expand on the author's doctoral research at Universiti Malaysia Sarawak, which examines speaking strategies, anxiety, motivation, and attitudes among Chinese undergraduates. This study highlights the importance of cultural factors in shaping language learning motivation, with implications for language policy and EFL research.